Imperial Identity in the Mughal Empire : Memory and Dynastic Politics in Early Modern South and Central Asia. - Balabanlilar, Lisa (I.B. Tauris & Company, Limited, 2015)
The last survivors of the House of Timur, the Mughals drew invaluable political capital from their lineage. Lisa Balabanlilar here positions the Mughal dynasty at the centre of the early modern Islamic world as the direct successors of a powerful political and religious tradition.